DEMOCRATIC MANAGEMENT IN CHILD EDUCATION - Nascimento, Leandra Fernandes do; Cavalcanti, Maria Marina Dias (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The Democratic Management was applied in Early Childhood Education, using its various legal instruments. The objective of this study is to know the process of Democratic Management in Early Childhood Education. The qualitative research approach was adopted, delineating it in a case study, in order to allow the researcher to know and reflect on the theoretical and practical context of the management in the School. It was verified that Democratic Management in Early Childhood Education is characterized by the effective participation of all those involved in the educational process and that this stage of education has undergone several transformations in the last decades, being supported by several legal devices, in order to improve the work. It is concluded that only the effective participation of the agents of the school community, in partnership with public agencies, will be able to overcome the educational challenges.